Species Diversity of Carp, Cyprinus carpio (Cypriniformes, Cyprinidae), Parasites in Some Cultivation Regions - Davydov, O.N.; Lysenko, V.N.; Kurovskaya, L.Ya. (Вестник зоологии, 2011)
Zoogeographical comparison for species diversity of carp parasites in different cultivation regions including aquatic ecosystems of Ukraine, Uzbekistan, Russia, and Vietnam was carried out. Totally, 160 parasitic species were recorded in carp within these regions. Parasitic species with direct and complex life cycles important in epizootic, veterinary, and health areas were registered. Проведено зоогеографическое сравнение особенностей видового разнообразия паразитов карпа из разных регионов разведения, включая водные экосистемы Украины, Узбекистана, России, Вьетнама. Всего у карпа в пределах этих регионов зарегистрировано 160 видов паразитов. Отмечены специфические и имеющие эпизоотологическое и медико-ветеринарное значения виды паразитов с прямым и сложным циклом развития.